Impactos dos metais e do câmbio na indústria brasileira - Bueno, Tulio de Carvalho Pinto (2007)
In the recent years, the rise in the commodities prices is being followed by an appreciation of the real exchange rate of the main exporters of this kind of product, including the Brazilian exchange rate. With an apparently appreciated exchange rate and a very small GDP growth rate, the macroeconomic policy is criticized for the level of the currency and the consequences for the industry. The objective of this work is to analyze the relation between the metal commodity’s price and the real exchange rate of many countries, especial the Brazilian exchange rate. With this relation pointed the paper will try to find evidences of the impact, direct or indirect, by the exchange rate, of this rise in the metal commodities price in the Brazilian industry. The result suggests that the rise in the metal commodities prices was really relevant for the appreciation in many currencies and also to Brazilian one. Even that we could find some sectors with long term impact derived from the rise of prices or appreciation of the currency there is no big evidence that points to a Dutch Disease, what would be viewed as a generalized deterioration of the Brazilian industry